16^2m/8^2n÷4^m×4^2(n-m+1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 04:51:16
16^2m/8^2n÷4^m×4^2(n-m+1)16^2m/8^2n÷4^m×4^2(n-m+1)16^2m/8^2n÷4^m×4^2(n-m+1)原式=2^8m/2^6n÷2^2m×2^4(n-m
16^2m/8^2n÷4^m×4^2(n-m+1)
16^2m/8^2n÷4^m×4^2(n-m+1)
16^2m/8^2n÷4^m×4^2(n-m+1)
原式=2^8m/2^6n÷2^2m×2^4(n-m+1)
=2^(8m-6n)÷2^2m×2^4(n-m+1)
=2^(8m-6n-2m+4n-4m+4)
=2^(2m-2n+4)
原式=2^8m/2^6n÷2^2m×2^4(n-m+1)=2^(8m-6n-2m+4n-4m+4)=2^(2m-2n+4)
[(m+n)(m-n)-(m-n)²+2n(m-n)]÷4n
1/(m-n)-1/(m+n)-2n/(m^2+n^2)-4n^3/m^4+n^4)-8n^7/(m^8+n^8)-16n^15/(m^16+n^16)+32n^31/(n32-m32)
[2(m+n)^5-3(m+n)^4+(-m-n)^3]÷[2(m+n)^3]
【(m+n)(m-n)-(m-n²)+2n(m-n)】÷4n
(n/m+n/2m^2)*4m/n^2
[(m-n)^2*(m-n)^3]^2/(m-n)^4
[(m-n)^2*(m-n)^3]^2/(m-n)^4
4m^2(m+n)-9n^2(m+n)
因式分解4m^2(m-n)+4n(n-m)
4m(m-n)^2+4n(n-m)^3
(m-n)2(n-m)3(n-m)4化简
(m-n)^2*(m-n)^4=?
化简,1.[(m+n-p)(m+p+n)-(m+n)²]/(-p),2.[(m+n)(m-n)-(m-n)²+2n(m-n)]/4n
16^2m ÷ 8^2n ÷ 4^m ×(125/4)^m-n
16^2m÷8^2n÷4^m×4^3m-3n+1
4m(m-m)-2n(n-m)
16^2m/8^2n÷4^m×4^2(n-m+1)
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=